2017
DOI: 10.13075/ijomeh.1896.00961
|View full text |Cite
|
Sign up to set email alerts
|

Screening survey of ocular, nasal, respiratory and skin symptoms in manicurists in Poland

Abstract: Objectives: Manicurists are exposed to various chemicals in nail and skin care products and may develop ocular, nasal, respiratory or skin adverse reactions to them. To investigate the occurrence of ocular, nasal, respiratory and skin problems among manicurists and to identify their causal factors, particularly allergic etiology and occupational origin. Material and Methods: Manicurists employed in beauty salons in the central region of Poland were invited to fill in the questionnaire and undergo medical exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Similarly, another study among 159 Korean nail salon technicians (98% female) from 120 salons reported frequent respiratory-related symptoms, including nose (odds ratio, OR 54.0; 95% confidence interval, CI 21.6 to 134.8) and throat irritation (OR 4.3; CI, 2.2 to 8.5) compared to controls (non-exposed office workers), after adjusting for relevant confounders [34]. Kiec-Swierczynska et al [52] captured information on respiratory symptoms (defined as wheezing and rales, chronic non-infection related cough, dyspnea) and other outcomes (ocular, nasal) during medical interviews among 93 Polish nail salon workers. Nail salon workers attributed several respiratory symptoms with exposure to nail dust, acrylic products, polish removers, disinfectants, and nail glues.…”
Section: Nail Salon Workersmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, another study among 159 Korean nail salon technicians (98% female) from 120 salons reported frequent respiratory-related symptoms, including nose (odds ratio, OR 54.0; 95% confidence interval, CI 21.6 to 134.8) and throat irritation (OR 4.3; CI, 2.2 to 8.5) compared to controls (non-exposed office workers), after adjusting for relevant confounders [34]. Kiec-Swierczynska et al [52] captured information on respiratory symptoms (defined as wheezing and rales, chronic non-infection related cough, dyspnea) and other outcomes (ocular, nasal) during medical interviews among 93 Polish nail salon workers. Nail salon workers attributed several respiratory symptoms with exposure to nail dust, acrylic products, polish removers, disinfectants, and nail glues.…”
Section: Nail Salon Workersmentioning
confidence: 97%
“…Five articles [34,[51][52][53][54] assessed respiratory outcomes among nail salon workers (Table 3). One US study [54] surveyed 61 female Southeast Asian immigrant nail salon workers in Oregon.…”
Section: Nail Salon Workersmentioning
confidence: 99%
“…Three acrylates may be present in some UV-gloss coatings used to coat beer can cartons: HDDA, TMPTA, and TPGDA. Acrylate exposure has been associated with allergic reactions, including allergic contact dermatitis, respiratory symptoms, and irritant symptoms [Kieć-Świerczyńska et al 2017;Sasseville 2012;Walters et al 2017]. We did not detect TMPTA in the bulk particulate samples we took, although small quantities of other acrylates were detected.…”
Section: Respiratory Healthmentioning
confidence: 58%
“…Acrylates, benzophenones, and certain metals have been described as potent skin sensitizers [Dittmer et al 2018;Greenspoon et al 2013;Hernando et al 2013;Karlsson et al 2011;Kieć-Świerczyńska et al 2017;Sasseville 2012;Sasseville et al 2011]. We asked all participants if they had experienced dermatitis in the past 12 months, or since starting work at the brewery if less than 12 months.…”
Section: Dermatitismentioning
confidence: 99%
“…During a similar period, 2353 patients were patch tested in a Spanish multi-centre study, and 43 (1.82%) were diagnosed with ACD caused by (meth)acrylates in long-lasting nail polish; all were female, and all had hand dermatitis [ 119 ]. A Polish study found contact dermatitis reported by 43% of nail technicians participating in a survey [ 120 ].…”
Section: Resultsmentioning
confidence: 99%